Serum glypican-4 is a marker of future vascular risk and mortality in coronary angiography patients. (March 2022) - Muendlein, Axel; Brandtner, Eva Maria; Leiherer, Andreas; Geiger, Kathrin; Heinzle, Christine; Gaenger, Stella; Fraunberger, Peter; Mader, Arthur; Saely, Christoph H.; Drexel, Heinz
Abstract: Background and aims: Glypican-4 (GPC4) is a cell surface protein, but can be released into circulation under various clinical conditions. The association of circulating GPC4 with the risk of future cardiovascular events or death is unclear. In the present study, we aimed to investigate the association between serum GPC4 and major adverse cardiovascular events (MACE), vascular mortality, and all-cause mortality in a prospective cohort study. Methods: Our study included 760 patients undergoing coronary angiography. During a mean follow up period of 6.3 years, the incidence of MACE, vascular mortality, and all-cause mortality was recorded. Serum GPC4 levels were determined using an enzyme-linked immunosorbent assay. Results: Serum GPC4 was highly significantly associated with increased age, body mass index, brain natriuretic peptide, and oxidized low density lipoprotein, as well as with decreased estimated glomerular filtration rate. During the follow-up period, 145 patients died, including 67 vascular deaths. MACE occurred in 137 patients. Serum GPC4 was significantly associated with MACE, vascular mortality, and all-cause mortality independently of traditional cardiovascular risk factors, with adjusted hazard ratios (HR) and 95% confidence intervals for one standard deviation change of serum GPC4 of 1.32 [1.10–1.58], 1.38 [1.06–1.78], and 1.53 [1.29–1.82], respectively. The best cut-off value for serum GPC4 for predicting MACE, vascular mortality, and all-cause mortality was 7.24 ng/ml for all three endpoints. Respective adjusted HRs were 1.61 [1.07–2.43], 2.85 [1.62–5.01], and 2.92 [2.00–4.27]. Conclusions: Our study indicates that elevated serum GPC4 levels are significantly associated with an increased risk of MACE, vascular mortality, and all-cause mortality. Graphical abstract: Image 1 Highlights: Serum levels of GPC4 are associated with traits linked to insulin resistance or obesity. Serum levels of GPC4 predict future major adverse cardiovascular events and mortality. Serum levels of GPC4 predict risk independently of traditional cardiovascular risk factors. Serum levels of GPC4 add additional predictive value to a basic model for mortality.